THE SOCIO-ECONOMIC ASPECT OF THE LIFELONG LEARNING BASED ON COMPETENCIES - Zenčaka, Andra; Silakalne - Arāja, Daina; Šenfelde, Maija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Generation of the 21st century threatened by many global problems: ecological, demographic, resource crisis, and also social conflicts. Therefore it becomes urgent the need for learning, regardless of age. As stated in the Latvian Sustainable Development Strategy, highly educated workforce training, the state human capital investments, public motivations in learning should be considered as a decisive aspect of the Latvian long-term economic improvement of the 21st century in order to ensure the competitiveness of the Latvian economy on a global scale. The aim of this article is to analyses the competence-based lifelong learning development’s possibilities in human capital and society in general, affecting green, competitive economy, where the country's internal resources are effectively used without threatening a capability of future generations to satisfy their requirements. The authors of a research have used the scientific analysis of literature, life-long learning policy issues in the international and national documents and expert evaluations, and also methods of processing of statistical data. The most fundamental problem in the article is the long-term economic growth in Latvia based on the skills and knowledge. It was emphasized in "EU 2020 strategy" also. According to the author’s conclusions, lifelong learning needs an improvement for achievement the new long-term objectives of the education system. Recommendations for the improvement of the lifelong learning for low-skilled workers and for the development of competencies of small and medium enterprises employees will be provided in the article.